2018
DOI: 10.3390/f9010047
|View full text |Cite
|
Sign up to set email alerts
|

Temperate and Tropical Forest Canopies are Already Functioning beyond Their Thermal Thresholds for Photosynthesis

Abstract: Tropical tree species have evolved under very narrow temperature ranges compared to temperate forest species. Studies suggest that tropical trees may be more vulnerable to continued warming compared to temperate species, as tropical trees have shown declines in growth and photosynthesis at elevated temperatures. However, regional and global vegetation models lack the data needed to accurately represent such physiological responses to increased temperatures, especially for tropical forests. To address this need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 100 publications
(181 reference statements)
7
56
0
1
Order By: Relevance
“…For example, the morning rise in PAR also corresponds with the morning peak in soil respiration, which could be an indication of photosynthetic activity influencing soil respiration. Further, midday decreases in RH roughly correspond to the midday depression of soil respiration, which could be a reflection of stomatal closure and reduced photosynthetic rates, especially when canopy temperatures are above optimum (>30 °C; Mau et al, 2018). During evening hours, when photosynthesis is not occurring, we observed a linear decline of soil respiration rates as temperatures cooled, which could reflect either a slowing of microbial activity in response to temperature, and/or a slowing of carbon supply to roots as photosynthesis stops.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the morning rise in PAR also corresponds with the morning peak in soil respiration, which could be an indication of photosynthetic activity influencing soil respiration. Further, midday decreases in RH roughly correspond to the midday depression of soil respiration, which could be a reflection of stomatal closure and reduced photosynthetic rates, especially when canopy temperatures are above optimum (>30 °C; Mau et al, 2018). During evening hours, when photosynthesis is not occurring, we observed a linear decline of soil respiration rates as temperatures cooled, which could reflect either a slowing of microbial activity in response to temperature, and/or a slowing of carbon supply to roots as photosynthesis stops.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, previous studies found that experimental warming of tropical tree seedlings had no effect on their PHTs (Krause et al., 2010). Indeed, many tropical species are already operating above their temperature optima and maxima for carbon assimilation (Doughty & Goulden, 2009; Mau, Reed, Wood, & Cavaleri, 2018), which is partially influenced by PSII function and provides additional indirect evidence of their limited capacity to acclimate to higher temperatures. Nevertheless, we did measure PHTs during the hottest part of the year which should have minimized any potential effect of cool‐to‐warm season acclimation on our heat tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous in situ studies showing a lack of upregulation of net photosynthesis with warming (Doughty, 2011), evidence that tropical plants are operating near physiological thresholds (Doughty and Goulden, 2008;Mau et al, 2018), and the fact that tropical forests have evolved within a very narrow climatic envelope (Janzen, 1967), we expected these tropical shrubs to have limited photosynthetic acclimation potential. We further hypothesized that respiration would acclimate to experimental warming, as respiratory acclimation has been shown in tropical plants developed in situ (Slot et al, 2014).…”
Section: Vwc 20mentioning
confidence: 99%
“…In fact, due to their high leaf area index, the shaded canopy and understory leaves can contribute more than 50% of gross primary productivity of tropical forests (Chen et al, 2012;He et al, 2018). The role that shaded leaves play in tropical forest carbon cycling may further increase as temperatures rise if upper canopies surpass their thermal thresholds (He et al, 2018;Mau et al, 2018;Pau et al, 2018). Shaded leaves could continue to play an even larger role in forest carbon cycling if elevated CO 2 lowers transpiration (Kirschbaum and McMillan, 2018) and, therefore, evaporative cooling in the upper canopy leaves, as this could potentially further increase upper canopy leaf temperatures and reduce photosynthesis (Doughty and Goulden, 2008;Fauset et al, 2019).…”
Section: Introductionmentioning
confidence: 99%